Employing shells to eliminate concentration quenching in photonic upconversion nanostructure. Issue 23 (1st June 2017) - Zuo, Jing; Li, Qiqing; Xue, Bin; Li, Cuixia; Chang, Yulei; Zhang, Youlin; Liu, Xiaomin; Tu, Langping; Zhang, Hong; Kong, Xianggui
Abstract : NaErF4 @NaYF4 upconversion nanoparticle: A novel NaErF4 @NaYF4 core–shell nanostructure is designed to generate efficient monochrome red UC emission under the multi-band excitation (∼800 nm, ∼980 nm and ∼1530 nm). Abstract : It is generally accepted that a lanthanide ions based upconversion material follows an activator low doping strategy (normally <3 mol%), because of the restriction of the harmful concentration quenching effect. Here, we demonstrate that this limitation can be broken in nanostructures. Simply by using an inert shell coating strategy, the concentration quenching effect for the activator (Er 3+ ) could be eliminated and highly efficient upconversion luminescence realized in the activator fully doped nanostructure, e.g. NaErF4 @NaYF4 . More importantly, this novel nanostructure achieves some long-cherished desires, such as multiple-band co-excitation (∼800 nm, ∼980 nm and ∼1530 nm) and monochromic red emission. Proof-of-concept experiments are presented of the potential benefit of this structure in solar cells and anti-counterfeiting. This nanostructure offers new possibilities in realizing high upconversion emission and novel functionalities of lanthanide based nanomaterials.